Genotoxicity and cytotoxicity evaluation of sea cucumber (Stichopus horrens) protein hydrolysates - Obren James Kawanding,; Noriham Abdullah,; Zainon Mohd Noor,; Nooraain Hashim,; Nazamid Saari,; Mohd Fakharul Zaman Raja Yahya,; Mohd Faiz Foong Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Sea cucumber (Stichopus horrens) protein hydrolysates were known as a potential functional food source with angiotensinconverting enzyme (ACE) inhibitory. The genotoxicity properties of S. horrens protein hydrolysates have been investigated through two different in vitro tests: Ames test and in vitro micronucleus test while the cytotoxicity properties of S. horrens protein hydrolysate were assessed using neutral red test. The study was conducted at a concentration up to 8000 μg/ml, 80 μg/ml and 50 μg/ml for Ames test, in vitro micronucleus test and neutral red test respectively with and without metabolic activation. There were no increments in the number of revertant colonies observed at any concentrations of S. horrens protein hydrolysates with and without metabolic activation in all four strains of Salmonella typhimurium (TA98, TA100, TA1535 and TA1537) compared to the solvent control. In in vitro micronucleus test, S. horrens protein hydrolysate did not induce clastogenicity in V79 cell while in neutral red test, S. horrens protein hydrolysate did not show any cytotoxic effects on NIH/3T3 mouse fibroblast cell. In conclusion, S. horrens protein hydrolysates are safe in terms of genotoxic and cytotoxic hence have the potential to be used in pharmaceutical and food industries as functional ingredient.